2001
DOI: 10.1108/09576060110384280
|View full text |Cite
|
Sign up to set email alerts
|

The perspective of suppliers on lean supply in a developing country context

Abstract: This paper deals with the perspective of autoparts suppliers in the Brazilian automotive industry on advances and barriers to renewed buyer-supplier relations under lean production practices, as uncovered by a comprehensive case study research. Suppliers perceived advances in the relationships as far as operational issues were concerned, but less so in terms of strategic issues. They also identified both organizational, firm-specific barriers and environmental barriers originating in the peculiarities of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
1
24
0
3
Order By: Relevance
“…For example, Forker et al (1999) report that both parties have different views on the buyer's implementation of the supplier's development activities. Arkader (2001) has found that buyers' perspectives are different from suppliers' in regard to both the facilitators and the barriers of buyer-supplier relationships. For instance, buyers identify "problems due to environmental factors (especially, adverse logistics and tax systems)" as important barriers to cooperative relationships, while suppliers identify "organizational barriers (mainly, the existence of functional resistance and the loss of power by buyers in the purchasing departments)" (p. 92).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Forker et al (1999) report that both parties have different views on the buyer's implementation of the supplier's development activities. Arkader (2001) has found that buyers' perspectives are different from suppliers' in regard to both the facilitators and the barriers of buyer-supplier relationships. For instance, buyers identify "problems due to environmental factors (especially, adverse logistics and tax systems)" as important barriers to cooperative relationships, while suppliers identify "organizational barriers (mainly, the existence of functional resistance and the loss of power by buyers in the purchasing departments)" (p. 92).…”
Section: Introductionmentioning
confidence: 96%
“…E concluem que a maioria dos aspectos do fornecimento enxuto é aplicável, excluindo-se algumas características que devem ser adaptadas a esse tipo de instituição. Arkader (2001) também trabalha com fornecimento enxuto, apresentando as perspectivas atuais dos fornecedores na indústria automobilística brasileira. Macduffie & Helper (1997) mostram exemplos práticos da difusão de princípios enxutos na cadeia de suprimentos de uma grande empresa automobilística.…”
Section: Trabalhos Com Foco Em Outras áReas Da Empresa (Oa)unclassified
“…• Vários autores focalizam a ME dentro de contextos especí-ficos de certos países, como, por exemplo, China (Dong, 1995), Japão (Katayama & Bennett, 1996, Austrália (Sohal, 1996), Brasil (Arkader, 2001), Inglaterra (Dennis & Robinson, 2000), Índia (Gulyani, 2001) e Finlândia (Kosonen & Buhanist, 1994. Comparações entre os estudos em diferentes países podem ser realizados.…”
Section: Análise Qualitativa Dos Principais Assuntos E Objetivos Dos unclassified
“…Li et al, 2005;Shah and Ward, 2007;Olhager and Prajogo, 2012;Bortolotti et al, 2013), only a small number of empirical studies acknowledge or consider the conjoint positive effect. These studies include those by Arkader (2001), Simpson and Power (2005), Jayaram et al, (2008) and Moyano-Fuentes et al, (2012). However, they are limited in a number of ways including very small sample sizes (e.g.…”
mentioning
confidence: 99%
“…However, they are limited in a number of ways including very small sample sizes (e.g. Arkader, 2001) and consideration of only two of the factors. Moreover, within contemporary literature from the fields of supplier integration (e.g.…”
mentioning
confidence: 99%